2013
DOI: 10.4137/sart.s12129
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian Medical Students’ Opinions about Individuals who use and Abuse Psychoactive Substances

Abstract: Substance use disorders are prevalent in Nigeria. The number of available specialist health providers is inadequate to fill the treatment gap. Interventions can be provided by nonspecialist health providers and have been found to be beneficial. However, attitudes toward substance misuse and misusers can impede the provision of this service. We aimed to determine attitudes of medical trainees toward substance use by utilizing a modified form of the Substance Abuse Attitude Scale (SAAS). Medical students (n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Moreover, among students who use nicotine, higher levels of nicotine use were associated with the perception that addiction is understandable (moderate correlation). These findings are in line with previous findings that medical students with more positive expectancies of the effects of substance use more regularly use alcohol or other psychoactive substances, compared to those with more negative expectancies of the effects of substance use [28]. More positive expectancies on the effects of substance use and illness perceptions of addiction might therefore both relate to increased levels of substance use among students.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, among students who use nicotine, higher levels of nicotine use were associated with the perception that addiction is understandable (moderate correlation). These findings are in line with previous findings that medical students with more positive expectancies of the effects of substance use more regularly use alcohol or other psychoactive substances, compared to those with more negative expectancies of the effects of substance use [28]. More positive expectancies on the effects of substance use and illness perceptions of addiction might therefore both relate to increased levels of substance use among students.…”
Section: Discussionsupporting
confidence: 82%
“…In line with previous studies male students tended to report more substance use compared to females [28,31,33]. It has been shown that among male students the number of students who drink alcohol increases during their college years, but remains stable among females [33].…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the prevalence rate was within the ranges from estimated rates and studies done elsewhere. 12,14,22 While most of the students who admitted to Cannabis use in the last 12 months did not have CUD, this study elicited its presence in 4.7% of the participants, possibly because some students use cannabis occasionally, and for recreational and social reasons. Such motivation for Cannabis use has been found in earlier studies in Botswana.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, after complete review, 38 studies were included in the systematic review ( Figure 1 ). From them, 11 referring to Europe: 6 the United Kingdom, 13 18 2 Spain, 19 , 20 1 Croatia, 21 1 France, 22 and 1 Serbia 23 ; 13 to the United States 24 36 ; 8 to the Central and Southern America: 7 Brazil 37 43 and 1 Honduras 44 ; 4 to Asia: 2 India, 45 , 46 1 Iran, 47 and 1 Nepal 48 ; as well as 2 to Africa, Nigeria 49 , 50 ( Table 1 ). No study was identified for Oceania.…”
Section: Resultsmentioning
confidence: 99%